Treatment of palm oil mill effluent using chemical coagulation / Bob Kulleh Tony - Bob Kulleh Tony (Faculty of Plantation and Agrotechnology, 2015)
In this study, treatment of palm oil mill effluent (POME) was conducted using aluminium sulphate using jar test experiment. Jar test experiment was conducted using one factor at a time (OFAT) approach, which manipulates one factor at a time in order looking for the best or optimum value for each factor. Experiment using OFAT approach was conducted on 18 runs for each coagulant 3 times replication. F aluminium sulphate, the lowest colour obtained was 120 (ADMI) at 6.0 pH, coagulant dosage of 6ml at 30% molarity and flocculants dosage of 6ml at 0.5% molarity . The effectiveness of colour removal using alum is 92%. The economic importance from this study are at-the price of alum at RM3437.28 per day, polymer RM130.20 per day and the total to treat the palm oil mill effluent are RM3567.48.